Proceedings 2019 Network and Distributed System Security Symposium 2019
DOI: 10.14722/ndss.2019.23418
|View full text |Cite
|
Sign up to set email alerts
|

How Bad Can It Git? Characterizing Secret Leakage in Public GitHub Repositories

Abstract: GitHub and similar platforms have made public collaborative development of software commonplace. However, a problem arises when this public code must manage authentication secrets, such as API keys or cryptographic secrets. These secrets must be kept private for security, yet common development practices like adding these secrets to code make accidental leakage frequent. In this paper, we present the first large-scale and longitudinal analysis of secret leakage on GitHub. We examine billions of files collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Exposing hard-coded secrets, such as hard-coded keys, is not uncommon in GitHub: Meli et al [47] identified 201,642 instances of private keys, which included commonly-used API keys. Meli et al [47] reported 85,311 of the identified 201,642 instances of private keys to be Google API keys.…”
Section: Rq2: How Frequently Do Security Smells Occur For Infrastructmentioning
confidence: 99%
“…Exposing hard-coded secrets, such as hard-coded keys, is not uncommon in GitHub: Meli et al [47] identified 201,642 instances of private keys, which included commonly-used API keys. Meli et al [47] reported 85,311 of the identified 201,642 instances of private keys to be Google API keys.…”
Section: Rq2: How Frequently Do Security Smells Occur For Infrastructmentioning
confidence: 99%
“…job titles, and social media uniform resource locators. Meli et al 6 revealed the prevalence of checked credentials, such as passwords or application programming interface keys, by finding more than 100,000 GitHub repositories with credentials.…”
Section: From the Editorsmentioning
confidence: 99%
“…But at the same time, the entirety of the code, including the feature definitions, can be developed publicly without revealing any non-public information about the data. With this strategy, developers and maintainers must monitor submissions to ensure that data is not accidentally copied into source code files -a process that can be automated, similar to scanning for secure tokens and credentials [31,59].…”
Section: Privacymentioning
confidence: 99%